Myeloid cell-derived creatine in the hypoxic niche promotes glioblastoma growth - Rashidi, Aida; Billingham, Leah K.; Zolp, Andrew; Chia, Tzu yi; Silvers, Caylee; Katz, Joshua L.; Park, Cheol H.; Delay, Suzi; Boland, Lauren; Geng, Yuheng; Markwell, Steven M.; Dmello, Crismita; et al. (Cell Metabolism, 2024)
Glioblastoma (GBM) is a malignancy dominated by the infiltration of tumor-associated myeloid cells (TAMCs). Examination of TAMC metabolic phenotypes in mouse models and patients with GBM identified the de novo creatine metabolic pathway as a hallmark of TAMCs. Multi-omics analyses revealed that TAMCs surround the hypoxic peri-necrotic regions of GBM and express the creatine metabolic enzyme glycine amidinotransferase (GATM). Conversely, GBM cells located within these same regions are uniquely specific in expressing the creatine transporter (SLC6A8). We hypothesized that TAMCs provide creatine to tumors, promoting GBM progression. Isotopic tracing demonstrated that TAMC-secreted creatine is taken up by tumor cells. Creatine supplementation protected tumors from hypoxia-induced stress, which was abrogated with genetic ablation or pharmacologic inhibition of SLC6A8. Lastly, inhibition of creatine transport using the clinically relevant compound, RGX-202-01, blunted tumor growth and enhanced radiation therapy in vivo. This work highlights that myeloid-to-tumor transfer of creatine promotes tumor growth in the hypoxic niche.
CRIS-Team Scopus Importer:2024-03-07
Keywords: creatine metabolism; glioblastoma; myeloid cells; pseudopalisading necrosis